The effect of silicone gel breast prosthesis on the electron beam dose distribution - Uushona, Ndeshihafela Vera (University of Limpopo (Medunsa), 2009)
Introduction The primary role of breast cancer treatment with radiation is to deliver a sufficient radiation dose to the cancer cells without unduly causing biological damage to the healthy tissues. For over 50 years, electron beam therapy has been an important modality for providing an accurate dose of radiation to superficial cancers and disease and for limiting the dose to underlying normal tissues and structures in particular to boost the dose to the tumour bed and surgical scars after mastectomy. The Monte Carlo code MCNP5 was used to determine the effect of silicone gel breast prosthesis on the electron beam dose distribution. Materials and Method Percentage depth dose curves (PDD) for 6, 9, 12, and 15 MeV electron energies along the electron central axis depth dose distributions in a water phantom and with silicone prosthesis immersed in a water phantom were simulated using MCNP5. In order to establish the accuracy of the MCNP5 code, the depth dose curves obtained using MCNP5 were compared against the measured depth dose curves obtained from the Varian 2100C linear accelerator. The simulated depth dose curves with silicone prosthesis immersed in water were compared to the measured depth dose curves with the vi silicone prosthesis in water. The dose at the interface of the prosthesis with water was measured using thermoluminiscent dosimeters. Results The simulated and measured depth dose curve and the investigated dosimetric parameters are within 2%. Simulations in the presence of silicone showed a decrease in dose as the at the interface as the beam passes from the prosthesis to water for most energies however, for 15 MeV beam there is an increase in dose at the interface between the prosthesis and water and this was verified by physical measurements. Conclusion There were good correlations between the measured and MCNP simulated depth dose curve. Differences were in order of 2%. Small deviations occurred due to the fact that the simulations assumed a monoenergetic beam that exits the accelerator head, while in the measured results the beam exiting from the accelerator head includes scatted radiation from the collimators and the applicator. The presence of the prosthesis does not perturb the electron beam central axis depth dose curve however, the 15 MeV beam enhanced the dose in front of the interface between the prosthesis and water. Despite the limitations mentioned above MCNP5 results agree reasonably with the measured results. Hence, MCNP5 can be very useful in simulating electron percentage depth dose data.
Thesis --(MSc. (Medical Physics)), 2009.
Keywords: Silicone Gel Breast Prosthesis; Electron Beam